Malaria Screening Using Front-Line Loop-Mediated Isothermal Amplification: Fourteen-Month Experience in a Nonendemic Regional Hub-and-Spoke Laboratory Setting. Issue 5 (7th December 2020) - McGinnis, Eric; Chan, Geoffrey; Hudoba, Monika; Markin, Todd; Yakimec, Jim; Roland, Kristine
Abstract: Objectives: We implemented front-line loop-mediated isothermal amplification (LAMP)–based malaria screening in our nonendemic multicenter health region to reduce reliance on microscopy without sacrificing diagnostic efficiency. We aimed to evaluate changes in test volumes, positivity rates, turnaround times, and approximate labor time savings resulting from implementation of LAMP-based malaria testing to assess the efficacy of the novel testing algorithm in our regional hub-and-spoke testing model. Methods: We reviewed data generated from institutional malaria testing between 2016 and 2019, having implemented LAMP in October 2018 as a front-line screening test for all malaria investigations from our hub facility and investigations from satellite facilities with negative rapid diagnostic tests (RDTs) and microscopy. Results: Blood film microscopy and RDT workloads decreased substantially in the year following LAMP implementation (by 90% and 46%, respectively, ) despite similar numbers of patients tested and positivity rates for malaria compared with historical data. LAMP turnaround times (TATs) were comparable to historical TATs for RDTs, and TATs for RDTs and thick films did not increase with the change in workflow. Conclusions: LAMP was successfully implemented in our multicenter health region malaria diagnostic algorithm, significantly reducing reliance on microscopic evaluations and RDT and providing substantial labor time savings without compromising TATs.